2015
DOI: 10.1063/1.4913419
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of ultrathin black phosphorus on hexagonal boron nitride

Abstract: Ultrathin black phosphorus, or phosphorene, is a two-dimensional material that allows both high carrier mobility and large on/off ratios. Similar to other atomic crystals, like graphene or layered transition metal dichalcogenides, the transport behavior of few-layer black phosphorus is expected to be affected by the underlying substrate. The properties of black phosphorus have so far been studied on the widely utilized SiO2 substrate. Here, we characterize few-layer black phosphorus field effect transistors on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 23 publications
4
81
0
Order By: Relevance
“…The first point suggests that there is no electronic-structure downside to hBN-encapsulation, which is already known to protect BP from environmental interactions. 29,31,32 The second conclusion is especially relevant for optoelectronics, as it implies that hBN-spaced BP stacks have the same light-absorption properties as monolayer BP, with the essential difference that more photons are absorbed due to the increased thickness. Finally, since the operation of BP/hBN/BP as a TFET is based on quantum tunneling, instead of thermionic excitation of carriers, we encounter negative differential resistance (NDR) peaks 33 with peak-to-valley ratios (PVRs) comparable to those predicted for TMDC TFETs, 34 as well as subthreshold swings below the minimum theoretical limit for conventional field effect transistors.…”
mentioning
confidence: 99%
“…The first point suggests that there is no electronic-structure downside to hBN-encapsulation, which is already known to protect BP from environmental interactions. 29,31,32 The second conclusion is especially relevant for optoelectronics, as it implies that hBN-spaced BP stacks have the same light-absorption properties as monolayer BP, with the essential difference that more photons are absorbed due to the increased thickness. Finally, since the operation of BP/hBN/BP as a TFET is based on quantum tunneling, instead of thermionic excitation of carriers, we encounter negative differential resistance (NDR) peaks 33 with peak-to-valley ratios (PVRs) comparable to those predicted for TMDC TFETs, 34 as well as subthreshold swings below the minimum theoretical limit for conventional field effect transistors.…”
mentioning
confidence: 99%
“…3. Theoretical and experimental studies have shown that metastable oxygen adsorbed on the surface of few-layer BP will lead to p -doping upon exposure to air, but the adsorption can be removed during the annealing [13, 14], then leading to a reduction in p -doping. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[28] Nevertheless, their results appear slightly ambiguous because the contact and channel resistances are not separately claimed. [29] In this letter, we report the fundamental electrical degradation mechanism of BP transistors in terms of the contact and channel resistances, respectively.…”
Section: Introductionmentioning
confidence: 96%